Emotion vs. cognition - Experimental evidence on cooperation from the 2014 Soccer World Cup - Johann Graf Lambsdorff; Marcus Giamattei; Katharina Werner; Manuel Schubert (Universität Passau, Wirtschaftswissenschaftliche Fakultät, 2016)
We investigate methods for stimulating cooperation by help of a controlled lab-inthefield experiment. This allows us to compare group-related emotional and cognitive stimuli. The experiment was carried out in a sober classroom and in an emotionally loaded environment, a Bavarian beer garden during a public viewing event with a large screen displaying the soccer game. Contrary to widespread belief, we do not find shared and contagious emotions at the public viewing event to advance cooperation. Variations of the game reveal that only cognitive factors, namely the joint attention to a common goal, substantially increase cooperation.
Keywords: 330